Analysis of coupled acoustic and drift modes leading to modons in Maxwellian and non-Maxwellian dusty plasma - Zahida Ehsan; Nazia Batool; V. M. Lashkin (AIP Advances)
Linear and nonlinear acoustic and drift waves in a confined inhomogeneous dusty plasma are investigated here. We examine two distinct scenarios that correspond to slow and fast temporal dynamics. The dust particles are inert in the first scenario, but actively participate in the dynamics in the second. Accordingly, we distinguish between the coupled dust-modified ion-acoustic and drift waves and coupled ultra-low-frequency dust acoustic and dust drift waves. The corresponding dispersion relations were determined in both situations by using linear analysis. In addition, nonlinear coherent structures known as “modons” or dipole vortices (cyclone–anticyclone pairs) have been identified in both circumstances, along with modons of higher orders. Moreover, as space observations of particle velocity distributions show the presence of either suprathermal tails or shoulders at low energy, we also expand our study for a special example of non-Maxwellian (Kappa and Cairns) dusty plasma. Numerical analysis shows the formation of vortices is impacted by nonthermality. The astrophysical and laboratory contexts provide a useful perspective on the significance of this analysis.